REPRESENTASI LOCAL WISDOM DALAM KARAWITAN MELALUI LAGU GARUDA PANCASILA SEBAGAI UPAYA MEMPERKUAT IDENTITAS BANGSA DI KALANGAN PEMUDA-REMAJA - Setya Rahdiyatmi Kurniajati Linuar (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2020)
The development of science and technology and the rapid flow of globalization have indirectly resulted in the degradation of values and the erosion of national identity, especially among youth. Youth become